Effect of ambrisentan on peripheral circulation in patients with systemic sclerosis. Issue 3 (3rd May 2016) - Sumida, Hayakazu; Asano, Yoshihide; Hatano, Masaru; Aozasa, Naohiko; Toyama, Tetsuo; Akamata, Kaname; Miyazaki, Miki; Taniguchi, Takashi; Takahashi, Takehiro; Ichimura, Yohei; Noda, Shinji; Kuwano, Yoshihiro; et al.
Abstract : Systemic sclerosis (SSc) is characterized by disturbed blood circulation. The effect of ambrisentan, an endothelin-A receptor-selective antagonist, on impaired peripheral circulation in SSc remains largely elusive. Here we show SSc patients, whose clinical symptoms such as cyanosis and Raynaud's phenomenon, were ameliorated by the treatment with ambrisentan. Additionally, objective evaluations with thermography showed improvement of hand coldness in steady-state and cold challenge tests. Ambrisentan might have a potential to improve peripheral circulation in SSc.